Lpsc-based solid-state electrolyte and continuous preparation method and application thereof

CN122916073APending Publication Date: 2026-10-16HUBEI XINGFA CHEM GRP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611205620.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0008]本发明的目的在于克服上述技术不足,提供一种LPSC基固态电解质及其连续化制备方法和应用,解决现有技术中难以连续化制备LPSC基固态电解质,且对产物的形貌调控能力有限导致离子电导率偏低的技术问题

Benefits of technology

本发明经前驱体浆料连续配制、连续式造粒形成球形前驱体颗粒以及连续烧结得到目标产物,全流程在密闭惰性气氛保护下连续运行,无需中间物料离线转移,能够缩短工艺周期,降低能耗,提高批次稳定性;同时本发明烧结过程中的惰性保护气体中还引入微量H2S气体,以抑制烧结过程中硫元素的挥发,在不对设备和操作安全性造成显著负担的前提下,有效抑制了硫缺陷的生成,提高电化学性能,尤其是电解质的离子电导率和电化学稳定性。本发明方法生产效率高、绿色环保,具备良好的工业化放大前景,制备的LPSC基固态电解质可广泛应用于全固态锂金属电池,提升电池综合性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916073A_ABST
    Figure CN122916073A_ABST
Patent Text Reader

Abstract

The application relates to an LPSC-based solid electrolyte and a continuous preparation method and application thereof, and comprises the following steps: under the protection of an inert atmosphere, taking a lithium source, a phosphorus source, a sulfur source and a chlorine source as raw materials, continuously mixing and dispersing the raw materials with an organic solvent under a closed condition to obtain a precursor slurry; continuously pumping the precursor slurry into a granulating device to perform granulation under the atmosphere of an inert carrier gas, and obtaining precursor particles; continuously feeding the precursor particles into a sintering furnace, introducing a protective gas containing 0.1-5 vol% H2S, and sequentially performing preheating, sintering and cooling to obtain the LPSC-based solid electrolyte. The whole process of the application is continuously operated under the protection of an inert atmosphere, intermediate materials are not required to be transferred offline, the process cycle is shortened, energy consumption is reduced, and batch stability is improved; trace H2S gas is introduced in the sintering process to inhibit the generation of sulfur defects and improve the electrochemical performance; the method has high production efficiency and good industrial amplification prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid electrolytes, specifically to an LPSC-based solid electrolyte and its continuous preparation method and application. Background Technology

[0002] This sulfide solid electrolyte has a high ionic conductivity (up to >10 mS·cm). -1 With its excellent mechanical ductility, Li6PS5Cl (LPSC) can be easily brought into close contact with the positive electrode active material through simple cold pressing, making it a research hotspot in the field of all-solid-state batteries. Among them, Li6PS5Cl (LPSC), as a representative system of sulfide solid electrolytes of the silver-germanium sulfide type, has the advantages of both high ionic conductivity and relatively low cost, and is one of the sulfide solid electrolyte systems with the most promising prospects for industrialization.

[0003] Currently, the conventional preparation method for LPSC-based solid electrolytes mainly adopts an intermittent process route combining solid-state ball milling and high-temperature sintering. Specifically, lithium sources (such as Li2S), phosphorus sources (such as P2S5), and chlorine sources (such as LiCl) are usually mixed in stoichiometric ratios and mechanically ball-milled for a long time (usually 10–40 hours) in a high-energy ball mill to obtain amorphous precursor powder. The precursor powder is then pressed into sheets and placed in a tube furnace for high-temperature sintering at 400–600°C under an inert atmosphere. After sintering, the mixture is naturally cooled to room temperature and then subjected to post-processing steps such as crushing and grading to obtain the LPSC solid electrolyte product.

[0004] The aforementioned intermittent process has the following drawbacks: First, high-energy ball milling is time-consuming and energy-intensive, with limited batch throughput, making it difficult to meet the capacity and cost requirements of large-scale industrial production. Second, intermittent operation leads to significant fluctuations in product quality between different batches, making it difficult to guarantee batch stability. Third, frequent material transfers are required between each process, from mixing, ball milling, sintering to crushing and grading, which not only increases operational complexity and labor costs but also inevitably introduces impurities and side reactions during each material transfer due to the extreme sensitivity of sulfide electrolytes to air and moisture, resulting in a decline in product performance. Fourth, in the existing process, the preparation of the precursor is separated from the high-temperature sintering step, lacking the ability to control the product morphology, particle size distribution, and crystal structure evolution in real time, which limits further optimization of the performance of LPSC-based solid electrolytes.

[0005] To address the aforementioned issues, exploratory research on continuous or semi-continuous preparation methods has emerged in recent years. For example, one patent discloses a method for preparing spherical solid electrolytes using spray drying technology. This method involves spray drying a raw material solution to obtain an intermediate powder, which is then heat-treated to obtain a sulfide-based solid electrolyte. However, this method's spray drying process only covers solvent removal and precursor morphology control, failing to achieve continuous high-temperature crystallization. The intermediate still needs to be separately transferred to a tube furnace for heat treatment, thus failing to achieve true end-to-end continuous production. Another example is a patent proposing a method for preparing composite solid electrolyte membranes using a twin-screw extruder. However, its core lies in the extrusion film formation of the composite material, rather than the continuous synthesis of the electrolyte powder material itself. Yet another example is Envision Power's disclosure of a method for preparing solid electrolyte membranes using gradient heating. This involves coating a precursor slurry and then sequentially heating and drying it at multiple temperature stages to achieve simultaneous solvent evaporation and electrolyte synthesis. However, this method is only suitable for preparing thin-film solid electrolytes and not for the large-scale production of powder-based LPSC solid electrolytes. Furthermore, Shenzhen University has disclosed a method for the large-scale rapid preparation of sulfide-based all-solid-state electrolytes, employing ultra-high-speed shear mixing to replace the traditional ball milling process, thus shortening the mixing time. However, the subsequent cold pressing, sintering, and pulverizing processes remain intermittent, failing to achieve a fully continuous process. Therefore, existing technologies lack a method for preparing LPSC-based solid-state electrolytes that can achieve a continuous process from raw material input to product output, and allows for precise control over the morphology, particle size distribution, and crystal phase structure of the product.

[0006] The core technical challenge of achieving continuous operation of sulfide solid electrolyte processes lies in the fundamentally conflicting requirements of each step regarding atmosphere, temperature, and material morphology. Precursor slurry preparation requires a liquid-phase environment, spray granulation necessitates rapid drying in a high-temperature carrier gas, while high-temperature crystallization sintering requires prolonged holding in a strictly temperature-controlled inert atmosphere—these three processes have drastically different requirements for material state (slurry → powder → sintered body) and process conditions. Material transfer between steps inevitably involves atmosphere exposure and temperature fluctuations. Therefore, continuous operation is not simply a matter of connecting equipment in series; it requires online conversion of material morphology and seamless integration of process conditions under closed conditions. This places systematic demands on precise atmosphere control, coordinated matching of multiple temperature zones, and the continuous and stable operation of the material conveying system.

[0007] Therefore, providing a continuous preparation method for LPSC-based solid electrolytes that can overcome the above-mentioned defects has become an urgent technical problem to be solved in this field. Summary of the Invention

[0008] The purpose of this invention is to overcome the above-mentioned technical deficiencies and provide an LPSC-based solid electrolyte and its continuous preparation method and application, solving the technical problems of the difficulty in continuously preparing LPSC-based solid electrolytes in the prior art and the limited ability to control the morphology of the product, resulting in low ionic conductivity.

[0009] To achieve the above-mentioned technical objectives, the technical solution provided by this invention is as follows: In a first aspect, the present invention provides a continuous preparation method for LPSC-based solid electrolyte, comprising the following steps: S1, under an inert atmosphere, lithium source, phosphorus source, sulfur source and chlorine source are taken as raw materials and continuously mixed and dispersed with an organic solvent under closed conditions to obtain an LPSC precursor slurry; S2, the LPSC precursor slurry is continuously pumped into a granulation device and granulated under an inert carrier gas atmosphere to obtain LPSC precursor particles; S3, the LPSC precursor particles are continuously fed into a sintering furnace, a protective gas containing 0.1-5 vol% H2S is introduced, and the mixture is preheated, sintered and cooled sequentially to obtain an LPSC-based solid electrolyte.

[0010] Secondly, the present invention provides an LPSC-based solid electrolyte prepared by the above-mentioned continuous preparation method, with a particle size D50 of 5 to 20 μm and a particle size distribution Span value ≤ 1.2.

[0011] Thirdly, the present invention provides an application of the above-mentioned LPSC-based solid electrolyte in the preparation of all-solid-state lithium metal batteries.

[0012] Compared with the prior art, the beneficial effects of the present invention include: This invention involves the continuous preparation of precursor slurry, continuous granulation to form spherical precursor particles, and continuous sintering to obtain the target product. The entire process operates continuously under a closed, inert atmosphere, eliminating the need for offline transfer of intermediate materials. This shortens the process cycle, reduces energy consumption, and improves batch stability. Simultaneously, a trace amount of H2S gas is introduced into the inert protective gas during the sintering process to suppress sulfur volatilization. This effectively inhibits sulfur defect formation without significantly burdening equipment and operational safety, thereby improving electrochemical performance, particularly the ionic conductivity and electrochemical stability of the electrolyte. This method is highly efficient, environmentally friendly, and has excellent prospects for industrial scale-up. The prepared LPSC-based solid electrolyte can be widely used in all-solid-state lithium metal batteries, enhancing overall battery performance. Attached Figure Description

[0013] Figure 1 Here is a SEM image of the LPSC-based solid electrolyte prepared in Example 1; Figure 2 The XRD pattern of the LPSC-based solid electrolyte prepared in Example 1; Figure 3 Image showing the ionic conductivity of the LPSC-based solid electrolyte prepared in Example 1; Figure 4 This is a block diagram of the continuous preparation system for LPSC-based solid electrolytes of the present invention. Detailed Implementation

[0014] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0015] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the invention, are intended to cover non-exclusive inclusion.

[0016] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of the invention. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0017] The existing methods for preparing LPSC-based solid electrolytes have the following problems: First, the traditional batch ball milling-sintering process has a long preparation cycle, high energy consumption, and poor batch stability, making it difficult to meet the needs of large-scale industrial production; Second, in the existing process, the precursor preparation and high-temperature sintering steps are separated, and the material is transferred multiple times between processes, increasing the risk of sulfide electrolytes being oxidized by moisture and the introduction of impurities; Third, the existing methods have limited ability to control the morphology, particle size distribution, and crystal phase structure of the product, making it difficult to obtain LPSC electrolyte products with high ionic conductivity and excellent performance.

[0018] Therefore, this invention addresses the shortcomings of existing technologies, such as the difficulty in continuously preparing LPSC-based solid electrolytes and the limited ability to control the morphology of the products, which leads to low ionic conductivity.

[0019] In a first aspect, the present invention provides a continuous preparation method for LPSC-based solid electrolytes, comprising the following steps: S1, under the protection of an inert atmosphere, lithium source, phosphorus source, sulfur source and chlorine source are used as raw materials, and continuously mixed and dispersed with organic solvent under closed conditions to obtain LPSC precursor slurry. S2, continuously pump the LPSC precursor slurry into the granulation unit and granulate it under an inert carrier gas atmosphere to obtain LPSC precursor particles. S3, LPSC precursor particles are continuously fed into a sintering furnace, and a protective gas containing 0.1 to 5 vol% H2S is introduced. After preheating, sintering and cooling, LPSC-based solid electrolyte is obtained.

[0020] This invention involves the continuous preparation of precursor slurry, continuous granulation to form spherical precursor particles, and continuous sintering to obtain the target product. The entire process operates continuously under a closed, inert atmosphere, eliminating the need for offline transfer of intermediate materials. This shortens the process cycle, reduces energy consumption, and improves batch stability. Simultaneously, the inert protective gas used in the sintering process contains 0.1%–5% H₂S gas by volume to suppress sulfur volatilization during sintering. This effectively inhibits sulfur defect formation and improves electrochemical performance, particularly the ionic conductivity and electrochemical stability of the electrolyte, without significantly burdening equipment and operational safety. This method is highly efficient, environmentally friendly, and has excellent prospects for industrial scale-up. The prepared LPSC-based solid electrolyte can be widely used in all-solid-state lithium metal batteries, enhancing overall battery performance.

[0021] In some embodiments, in step S1, the lithium source is selected from at least one of lithium sulfide (Li2S), lithium chloride (LiCl), lithium hydroxide (LiOH·H2O), or lithium oxide (Li2O); the phosphorus source is selected from at least one of phosphorus pentasulfide (P2S5), phosphorus trisulfide (P2S3), or lithium phosphate (Li3PO4); the sulfur source is selected from at least one of lithium sulfide (Li2S), sulfur (S), or phosphorus pentasulfide (P2S5); and the chlorine source is selected from at least one of lithium chloride (LiCl) or ammonium chloride (NH4Cl).

[0022] In the preparation of LPSC (Li6PS5Cl) based solid electrolyte, lithium sulfide (Li2S), phosphorus pentasulfide (P2S5), and lithium chloride (LiCl) are preferably used as raw materials, and the materials are fed in a molar ratio of Li2S:P2S5:LiCl = (2~3):1:1.

[0023] Furthermore, lithium, phosphorus, sulfur, and chlorine sources are used as raw materials according to the stoichiometric ratio of LPSC-based solid electrolytes.

[0024] In some embodiments, in step S1, the chemical composition of the LPSC-based solid electrolyte further includes one or more doping elements, which are selected from at least one of Zn, F, Mo, In, Mg, O, Al, Si, and Ge. The doping elements are introduced by adding sulfides, oxides, fluorides, or chlorides of the corresponding doping elements during the mixing process in step S1.

[0025] In some embodiments, in step S1, the organic solvent is selected from at least one of anhydrous acetonitrile, tetrahydrofuran, ethyl acetate, propyl acetate, or toluene, and the amount of organic solvent used is 0.5 to 5 times the total mass of the raw materials.

[0026] In some embodiments, in step S1, the inert atmosphere includes argon.

[0027] In some embodiments, in step S1, the apparatus used for continuous mixing and dispersion is a high-shear homogenizer, a static mixer, or a tubular stirred ball mill, and the mixing and dispersion time is 5 to 60 minutes, during which the slurry temperature is maintained at 20 to 60°C.

[0028] In some embodiments, in step S2, the granulation device is a spray drying granulation device; the granulation conditions include: inlet temperature of 120-250°C, outlet temperature of 60-120°C, slurry feed rate of 5-100 mL / min, and atomization pressure of 0.1-0.5 MPa.

[0029] Furthermore, the spray drying granulation device is selected from centrifugal spray dryer, pressure spray dryer or airflow spray dryer, more preferably pressure spray dryer; organic solvents are recovered and reused during the spray drying granulation process.

[0030] In some embodiments, in step S2, the inert carrier gas atmosphere includes nitrogen or argon, with a flow rate of 1–20 m³ / h. 3 / h.

[0031] In some embodiments, in step S2, the LPSC precursor particles are spherical with a particle size D50 of 1–20 μm.

[0032] In some embodiments, in step S3, the LPSC precursor particles are continuously fed into the sintering furnace via a pneumatic conveying system or a screw feeder at a feed rate of 5 to 10 g / min.

[0033] In some embodiments, in step S3, the sintering furnace is a rotary tube furnace, which is equipped with a disturbance structure to promote the tumbling and mixing of materials and to make the materials spiral forward in the furnace. The rotation speed of the furnace tube is 1-20 r / min. This invention promotes continuous sintering of materials through a rotary tube furnace.

[0034] Furthermore, the disturbance structure is a spiral guide chute or staggered lifting plates set on the inner wall of the furnace tube.

[0035] In some embodiments, in step S3, the protective gas includes nitrogen, argon, or helium, with a total flow rate of 0.5 to 10 L / min.

[0036] In some embodiments, in step S3, the preheating temperature is 100–300°C and the time is 10–60 min; the sintering temperature is 400–650°C and the time is 30–180 min; the cooling outlet temperature is ≤60°C and the time is 10–60 min.

[0037] It should be noted that the sintering furnace of this invention is also equipped with multiple temperature control zones evenly distributed along the length of the furnace tube. Each temperature control zone independently controls the temperature to achieve a temperature gradient distribution for preheating, sintering, and cooling. The preheating, sintering, and cooling of the LPSC precursor particles are all carried out continuously in the sintering furnace. Therefore, the time in each zone refers to its total residence time in that zone, for example, the total residence time in the sintering zone is 30 to 180 minutes.

[0038] In some embodiments, in step S3, the LPSC-based solid electrolyte is further subjected to pneumatic classification after discharge; the classification is carried out in a fluidized bed air classifier, and the particle size is controlled between 5 and 30 μm.

[0039] In this invention, the oxygen content in the inert atmosphere during each step is controlled to be ≤10 ppm and the moisture content is controlled to be ≤1 ppm.

[0040] Secondly, the present invention provides an LPSC-based solid electrolyte prepared by the above-mentioned continuous preparation method, with a particle size D50 of 5 to 20 μm and a particle size distribution Span value ≤ 1.2.

[0041] In some embodiments, the general chemical formula of the LPSC-based solid electrolyte is Li 6-y PS 5-y Cl 1+y Where 0 ≤ y < 1, and any doped element is selected; the LPSC-based solid electrolyte particles are spherical or near-spherical, and the ionic conductivity at 25℃ is 3–15 mS·cm. -1 .

[0042] Thirdly, the present invention provides an application of the above-mentioned LPSC-based solid electrolyte in the preparation of all-solid-state lithium metal batteries.

[0043] The main mechanisms of action of this invention include: See Figure 4This invention prepares LPSC precursor slurry through a continuous raw material mixing and dispersion unit 401. The LPSC precursor slurry is continuously pumped into a spray drying granulation device 403 via a slurry delivery pump 402. Spray drying granulation is performed under an inert carrier gas atmosphere provided by an inert carrier gas supply unit 404. The atomized droplets are rapidly dried to form spherical precursor particles. The spherical LPSC precursor particles are continuously fed into a multi-temperature zone rotary tube sintering furnace 406 via a closed continuous feeding unit 405. This sintering furnace is a dynamic tube sintering furnace, which can promote the tumbling and mixing of materials and allow the spherical LPSC precursor particles to pass through the preheating zone, sintering zone, and cooling zone in sequence. The crystallization sintering process is completed in a continuous manner in a protective gas containing 0.1-5 vol% H2S. The product is graded by a product pneumatic conveying unit 408 and an airflow classification unit 409, and collected by a product collection unit 410.

[0044] Through extensive experimentation, the inventors discovered a synergistic relationship among the following three factors: the particle size of the spray granulation precursor (D50 = 1–20 μm), the rotational speed of the dynamic tube furnace (1–20 r / min), and the residence time in the sintering zone (30–180 min). Too small a particle size leads to dust aggregation, while too large a particle size results in incomplete crystallization. Too low a rotational speed results in insufficient mixing, while too high a speed shortens the residence time and exacerbates wear. Too short a residence time leads to insufficient crystallinity, while too long a residence time results in excessive grain growth and a decrease in ionic conductivity. This invention optimizes these three factors synergistically to achieve ideal spherical morphology and particle size distribution while maintaining high crystallinity, thus optimizing ionic conductivity.

[0045] This invention introduces a protective gas of 0.1–5 vol% H2S in the sintering step (S3). Its core mechanism lies in the fact that H2S decomposes at high temperatures to generate sulfur vapor, thereby increasing the partial pressure of sulfur in the sintering system and suppressing the high-temperature volatilization of sulfur in the LPSC lattice. Sulfur vacancies are the main point defects in silver-germanium sulfide-type solid electrolytes; an increase in their concentration leads to lattice distortion, obstruction of lithium-ion migration channels (decreased ionic conductivity), and an increase in electronic conductivity (increased risk of self-discharge). This invention effectively suppresses the formation of sulfur defects by precisely controlling the H2S concentration within this specific range, without significantly burdening equipment and operational safety. It should be noted that the amount of H2S introduced is not necessarily better the higher it is—excessively high H2S partial pressure (e.g., ≥10 vol%) will disrupt the stoichiometric balance of the LPSC system, inducing the precipitation of impurity phases such as LiCl. The 0.1–5 vol% concentration range determined in this invention is the optimal window for this continuous process system.

[0046] The main advantages of this invention include: (1) The whole process is closed and continuous, which significantly improves production efficiency: The present invention can integrate precursor slurry preparation, spray granulation, dynamic tube furnace continuous sintering and product grading into a complete continuous process. From raw material input to product output, there is no need for offline transfer of intermediate materials and intermittent operation, which greatly shortens the preparation cycle (from 20-50 hours in the traditional process to 4-12 hours). At the same time, it significantly reduces energy consumption and labor costs, and has good prospects for industrial scale-up.

[0047] (2) Continuous protection throughout the entire process to ensure product quality: The entire process of this invention operates continuously under a controlled inert atmosphere. The spray granulation outlet and the dynamic tubular furnace inlet are seamlessly connected through a pneumatic conveying system, avoiding atmosphere exposure and temperature fluctuations caused by material transfer between processes in traditional intermittent processes. This effectively suppresses the deliquescence and oxidation side reactions of sulfide electrolytes, improving the batch stability and electrochemical performance consistency of the products. The pneumatic conveying system continuously introduces inert gas during the conveying process, keeping the precursor particles in a low-oxygen and low-water environment throughout the conveying process. This is a key structural design to ensure continuous operation of the entire process.

[0048] (3) Spray granulation to obtain spherical particles, optimize morphology and packing density: The present invention obtains spherical LPSC precursor particles through spray drying granulation technology. Compared with irregular block or sheet particles in traditional processes, spherical particles have better flowability and packing characteristics, which is conducive to achieving uniform filling and densification in subsequent sintering and downstream battery manufacturing processes. At the same time, spherical particles can reduce the contact stress between particles, which helps to improve the mechanical stability of the electrolyte layer.

[0049] (4) Dynamic tube furnace continuous sintering achieves precise control of the crystallization process: This invention adopts a rotary tube furnace with a multi-temperature zone design, which enables the precursor particles to be uniformly heated during dynamic tumbling, overcoming the defects of uneven heat transfer, local overheating and large batch-to-batch differences in traditional static sintering. By independently controlling the temperature and residence time of the preheating zone, sintering zone and cooling zone, the crystallinity, grain size and phase purity of the product can be precisely controlled, thereby achieving directional optimization of ionic conductivity.

[0050] (6) Atmosphere regulation to suppress sulfur defects and improve electrochemical performance: This invention introduces 0.1-5 vol% H2S into the protective atmosphere, thereby increasing the sulfur partial pressure in the sintering system, effectively suppressing the high-temperature volatilization of sulfur in the LPSC lattice, reducing sulfur vacancy defects, and avoiding problems such as lattice distortion, blocked lithium ion migration channels and increased electronic conductivity caused by sulfur vacancies, thus significantly improving the ionic conductivity and electrochemical stability of the electrolyte.

[0051] (7) Green and environmentally friendly process: The present invention uses organic solvent as dispersion medium and achieves solvent recovery and recycling through spray drying, resulting in low solvent loss; the dynamic tube furnace adopts a closed-loop inert gas protection system, which effectively suppresses the emission of harmful gases such as H2S during the sintering of sulfides.

[0052] The present invention will be further described in detail below through specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.

[0053] Example 1 A continuous preparation method for LPSC-based solid electrolytes includes the following steps: S1, Continuous preparation of precursor slurry: In a glove box filled with high-purity argon (oxygen content ≤ 5 ppm, water content ≤ 0.5 ppm), Li2S, P2S5, and LiCl raw materials were weighed according to the molar ratio Li2S:P2S5:LiCl = 5:1:2, with a total mass of 500 g. The above raw materials were transferred to the sealed feeding hopper of a high-shear homogenizer. Using propyl acetate at twice the total mass of the raw materials as a solvent, the high-shear homogenizer was turned on, and the rotation speed was controlled at 3000 rpm. The mixture was continuously mixed and dispersed at 25±5℃ for 20 min to obtain a uniformly dispersed LPSC precursor slurry.

[0054] S2, Spray granulation to form spherical precursor particles: The LPSC precursor slurry obtained in step S1 is continuously pumped into a pressure spray dryer at a feed rate of 20 mL / min using a peristaltic pump. The atomization pressure is 0.25 MPa, the inlet temperature is 200℃, the outlet temperature is 100℃, and the inert carrier gas is high-purity nitrogen with a flow rate of 5 m³ / min. 3 / h. The atomized droplets are rapidly dried in a hot nitrogen gas stream to form spherical LPSC precursor particles. The D50 of the obtained spherical precursor particles, as measured by an online laser particle size analyzer, is 8.5 μm. The particles are regular spherical in shape and have a smooth surface.

[0055] S3, Continuous Sintering in a Dynamic Tube Furnace: The spherical LPSC precursor particles obtained in step S2 are continuously fed into a rotary tube furnace at a feed rate of 8 g / min via a closed spiral feeder. The inner wall of the furnace tubes is equipped with spiral guide channels, and the furnace tubes rotate at 8 r / min. A protective gas of high-purity nitrogen containing 1 vol% H2S (total flow rate 3 L / min) is introduced into the furnace. The furnace tubes are divided into three temperature zones along their length: a preheating zone at 250°C with a residence time of approximately 20 min; a sintering zone at 550°C with a residence time of approximately 90 min; and a cooling zone where circulating cooling water lowers the furnace tube outlet temperature to below 50°C with a residence time of approximately 30 min. The precursor particles sequentially pass through the three temperature zones during dynamic tumbling, completing the crystallization and sintering process.

[0056] S4, Product Collection and Classification: LPSC solid electrolyte particles collected from the rotary tube furnace outlet are fed into a fluidized bed air classifier through a closed pneumatic conveying system. The particles are classified and cut to a size of 15μm to obtain LPSC-based solid electrolyte products with the target particle size distribution.

[0057] Product performance characterization: SEM photos such as Figure 1 As shown, the product particles are spherical or near-spherical with a dense surface.

[0058] ICP-OES analysis showed that the elemental composition of the LPSC solid electrolyte prepared in this example conformed to the stoichiometry of Li6PS5Cl.

[0059] XRD patterns as follows Figure 2 As shown, the product exhibits a pure phase silver-germanium sulfide structure (space group F-43m) with no impurity diffraction peaks.

[0060] Particle size analysis results showed D50=9.2μm, Span=1.05.

[0061] Ionic conductivity was determined using electrochemical impedance spectroscopy (EIS) at 25°C. Figure 3 As shown, the ionic conductivity is 16.1 mS·cm. -1 The electrochemical window was determined using linear sweep voltammetry (LSV) to be 5.2 V vs. Li. + / Li. The critical current density (CCD) test result is 1.5 mA·cm. -2 .

[0062] The continuous preparation process of this invention is compared with the traditional intermittent combined method, and the results are shown in Table 1.

[0063] Table 1. Overall Effects of End-to-End Continuity

[0064] As can be seen from the comparison in Table 1, the present invention significantly shortens the preparation cycle, increases batch capacity, eliminates exposure during product preparation, ensures good batch product consistency, and significantly reduces energy consumption and labor costs, thus possessing good prospects for industrial scale-up.

[0065] Example 2 This embodiment is basically the same as Embodiment 1, except that an additional doping source is added in step S1. Specifically, ZnS and LiF are added during the feeding stage, with doping amounts of 2.0 wt% and 1.5 wt% of the total solid mass, respectively. The other steps are consistent with Embodiment 1.

[0066] The ionic conductivity of the Zn / F co-doped LPSC-based solid electrolyte prepared in this embodiment was measured to be 5.2 mS·cm. -1 (25℃), the critical current density increases to 1.9 mA·cm. -2 The performance was significantly improved compared to the undoped sample.

[0067] Example 3 This embodiment is basically the same as Embodiment 1, except that some process parameters are adjusted. Specifically: in step S1, the amount of organic solvent is 0.5 times the total mass of the raw materials, and the mixing time is 5 min; in step S2, the feed rate is 5 mL / min, and the inlet temperature is 120℃; in step S3, the sintering zone temperature is 400℃, and the residence time is 30 min; in step S4, the particle size of the graded cutting is 30 μm.

[0068] The ionic conductivity of the LPSC solid electrolyte prepared in this example was measured to be 3.2 mS·cm. -1 The electrochemical window is 4.8 V vs. Li. + / Li still outperforms products produced by traditional batch processes.

[0069] Comparative Example 1 This comparative example is basically the same as Example 1, except that step S2 is omitted, and the precursor slurry obtained in step S1 is directly dried and then sent to the dynamic tube furnace in step S3 for sintering. The other steps are consistent with those in Example 1.

[0070] Measurements showed that the LPSC solid electrolyte particles prepared in this comparative example exhibited an irregular mixed morphology of blocks and sheets, with a low packing density. Higher pressing pressure is required in subsequent battery assembly to obtain a dense electrolyte layer. The ionic conductivity was 3.8 mS·cm. -1 This is lower than that of Example 1.

[0071] Comparative Example 2 This comparative example is basically the same as Example 1, except that in step S3, the rotary tube furnace is replaced with a conventional static tube furnace, and the precursor particles are spread in powder form in an alumina crucible and statically sintered under the same temperature profile and atmosphere conditions. The other steps are consistent with Example 1.

[0072] Measurements showed that the LPSC solid electrolyte particles prepared in this comparative example were irregular lumps with a wide particle size distribution (Span > 1.6). Obvious sintering necks and agglomeration were observed between the particles, requiring additional crushing treatment to obtain dispersed powder. The ionic conductivity was 3.2 mS·cm. -1 (25°C), significantly lower than 4.8 mS·cm in Example 1. -1 XRD results showed a small number of unreacted Li2S impurity peaks in the statically sintered samples, indicating that uneven heat transfer under static conditions led to incomplete reaction in some areas. This demonstrates that the material tumbling effect of dynamic sintering plays an irreplaceable role in ensuring complete reaction and consistent product performance.

[0073] Comparative Example 3 This comparative example is basically the same as Example 1, except that the residence time in the sintering zone is adjusted to 15 min or 240 min in step S3. Other steps are consistent with Example 1.

[0074] The product ionic conductivity was measured to be 2.8 mS·cm at a residence time of 15 min. -1 XRD analysis showed insufficient crystallinity and the presence of a large amount of amorphous phase; at a residence time of 240 min, the ionic conductivity of the product was 3.1 mS·cm. -1 The particles were excessively sintered, with a significantly increased particle size and abnormal grain growth. Both exhibited significantly lower performance than the 4.8 mS·cm of Example 1. -1 This indicates that there is an optimal window for sintering residence time.

[0075] Comparative Example 4 This comparative example is basically the same as Example 1, except that in step S3, the sintering atmosphere is replaced with pure high-purity nitrogen (without H2S doping), and the gas flow rate is 3 L / min. The other process parameters, raw material ratios, and equipment conditions are exactly the same as in Example 1.

[0076] The XRD pattern of the LPSC solid electrolyte prepared in this comparative example showed Li3PS4 and elemental sulfur impurities, with dense lattice defects; D50 = 10.1 μm, Span = 1.38; and an ionic conductivity of only 2.9 mS·cm at 25℃. -1 The current density decreased by 39.6% compared to Example 1; the critical current density was 1.1 mA·cm⁻¹. -2The batch-to-batch performance variation RSD > 12%. This result indicates that a pure nitrogen atmosphere without H2S protection cannot suppress the volatilization of sulfur during sintering, leading to a large number of sulfur vacancy defects in the crystal lattice, obstructing ion transport channels, and further degrading electrochemical performance due to the formation of impurity phases.

[0077] Comparative Example 5 This comparative example is basically the same as Example 1, except that the volume fraction of H2S in the protective atmosphere is increased from 1 vol% to 10 vol% in step S3. All other process parameters, raw material ratios, and equipment conditions are exactly the same as in Example 1. The phase composition, particle size distribution, and electrochemical performance of the LPSC solid electrolytes prepared at various H2S concentrations were measured, and the results are shown in Table 2 below. Table 2 Performance of LPSC solid electrolytes prepared with different H2S volume fractions under protective atmosphere

[0078] Measurements showed that when the volume fraction of H₂S increased to 10 vol%, the ionic conductivity of the product decreased to 3.9 mS·cm. -1 Further improvements resulted in a continued decrease in ionic conductivity and the appearance of obvious LiCl impurity phases or LiCl and Li2S impurity phases, with a significant widening of the particle size distribution.

[0079] In summary, the preparation method of this invention sequentially includes four steps: continuous preparation of precursor slurry, spray granulation to form spherical precursor particles, continuous sintering in a dynamic tube furnace, and product collection and classification. The entire process operates continuously under a closed, inert atmosphere, eliminating the need for offline transfer of intermediate materials. This invention solves the technical problems of long preparation cycles, high energy consumption, poor batch stability, and susceptibility to moisture and oxidation during material transfer in traditional batch processes. By optimizing particle morphology through spray granulation and precisely controlling the crystal phase structure through dynamic tube furnace sintering, a spherical LPSC-based solid electrolyte with uniform particle size distribution and high ionic conductivity is ultimately obtained. This method is highly efficient, environmentally friendly, and has good prospects for industrial scale-up. The prepared LPSC-based solid electrolyte can be widely used in all-solid-state lithium metal batteries to improve overall battery performance.

[0080] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A continuous preparation method for an LPSC-based solid electrolyte, characterized in that, Includes the following steps: S1, under the protection of an inert atmosphere, lithium source, phosphorus source, sulfur source and chlorine source are used as raw materials, and continuously mixed and dispersed with organic solvent under closed conditions to obtain LPSC precursor slurry. S2, continuously pump the LPSC precursor slurry into the granulation unit and granulate it under an inert carrier gas atmosphere to obtain LPSC precursor particles. S3, LPSC precursor particles are continuously fed into a sintering furnace, and a protective gas containing 0.1 to 5 vol% H2S is introduced. After preheating, sintering and cooling, LPSC-based solid electrolyte is obtained.

2. The continuous preparation method of LPSC-based solid electrolyte according to claim 1, characterized in that, In step S1, the lithium source is selected from at least one of lithium sulfide, lithium chloride, lithium hydroxide, or lithium oxide; The phosphorus source is selected from at least one of phosphorus pentasulfide, phosphorus trisulfide, or lithium phosphate. The sulfur source is selected from at least one of lithium sulfide, sulfur, or phosphorus pentasulfide. The chlorine source is selected from at least one of lithium chloride or ammonium chloride.

3. The continuous preparation method of LPSC-based solid electrolyte according to claim 1, characterized in that, In step S1, the chemical composition of the LPSC-based solid electrolyte also includes doping elements, which are selected from at least one of Zn, F, Mo, In, Mg, O, Al, Si, and Ge. The doping elements are introduced by adding sulfides, oxides, fluorides, or chlorides of the corresponding doping elements during the mixing process in step S1.

4. The continuous preparation method of LPSC-based solid electrolyte according to claim 1, characterized in that, In step S1, the organic solvent is selected from at least one of anhydrous acetonitrile, tetrahydrofuran, ethyl acetate, propyl acetate, or toluene, and the amount of the organic solvent used is 0.5 to 5 times the total mass of the raw materials. The inert atmosphere includes argon; The continuous mixing and dispersion process takes 5 to 60 minutes and is carried out at a temperature of 20 to 60°C.

5. The continuous preparation method of LPSC-based solid electrolyte according to claim 1, characterized in that, In step S2, the granulation is spray drying granulation; the granulation conditions include: inlet temperature of 120-250℃, outlet temperature of 60-120℃, slurry feed rate of 5-100 mL / min, and atomization pressure of 0.1-0.5 MPa. The inert carrier gas atmosphere includes nitrogen or argon, with a flow rate of 1–20 m³ / h. 3 / h.

6. The continuous preparation method of LPSC-based solid electrolyte according to claim 1, characterized in that, In step S2, the LPSC precursor particles are spherical with a particle size D50 of 1–20 μm.

7. The continuous preparation method of LPSC-based solid electrolyte according to claim 1, characterized in that, In step S3, the feed rate of the LPSC precursor particles into the sintering furnace is 5-10 g / min. The sintering furnace is a rotary tube furnace, and the rotation speed of the furnace tubes is 1 to 20 r / min.

8. The continuous preparation method of LPSC-based solid electrolyte according to claim 1, characterized in that, In step S3, the protective gas includes nitrogen, argon, or helium, with a total flow rate of 0.5–10 L / min; The preheating temperature is 100–300℃ and the time is 10–60 min; the sintering temperature is 400–650℃ and the time is 30–180 min; the cooling outlet temperature is ≤60℃ and the time is 10–60 min.

9. The LPSC-based solid electrolyte prepared by the continuous preparation method according to any one of claims 1-8, characterized in that, Its particle size D50 is 5 to 20 μm, and its particle size distribution Span value is ≤1.

2.

10. The application of the LPSC-based solid electrolyte as described in claim 9 in the preparation of all-solid-state lithium metal batteries.